Sistem Pakar Untuk Mendiagnosa Jenis-Jenis Penyakit Stroke Menggunakan Metode Variable-Centered Intelligent Rule System - Viyanti, Elvi Octa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Stroke is a disease that occurs due to blockage of the brain blood vessels or rupture of blood vessels in the brain. So that due to blockage or rupture of these blood vessels, certain parts of the brain are reduced and even the oxygen supply is cut off so that they become damaged and even die. Consulting with an expert is expensive. Sometimes sufferers are unable to consult their illness to an expert because of cost issues. In addition, it is difficult for sufferers to meet experts, especially in small areas. The few experts in the area make it even more difficult for the sufferer. Because there are few experts in the area, it requires the sufferer to seek experts in big cities. That of course requires a lot of money. The method used is the Variable-Centered Intelligent Rule System (VCIRS) method. The purpose of this research is to create an expert system that can work more than an expert and is expected to help the public to diagnose the type of stroke so that the treatment of the disease is faster and more accurate. The result of the research is an expert system application program that is able to diagnose the type of stroke. System output in the form of disease diagnosis results obtained by calculations using the Variable-Centered Intelligent Rule System (VCIRS) method and its solution.